2021
DOI: 10.1093/ecco-jcc/jjab154
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Injection in Crohn’s Disease Strictures: A Phase I–II Clinical Study

Abstract: Background and aim Mesenchymal stem cells (MSCs) have anti-inflammatory and anti-fibrotic properties and could be a potential therapy for Crohn’s Disease (CD) strictures. In this phase I–II pilot trial, we assessed safety and efficacy of local MSC injection to treat CD strictures. Methods CD patients with a short (less than 5 cm in length) non-passable stricture accessible by ileocolonoscopy were included. Allogenic bone-marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Similarly, the application of allogeneic UC-MSC exhibited safety, feasibility, limited or no adverse effects, and led to the improvement of clinical symptoms. However, no significant changes in the levels of inflammatory cytokines in blood serum were detected ( Hossein-khannazer et al, 2021 ; Vieujean et al, 2022 ).…”
Section: Specific Sections Dedicated To Pnd Applicationsmentioning
confidence: 97%
“…Similarly, the application of allogeneic UC-MSC exhibited safety, feasibility, limited or no adverse effects, and led to the improvement of clinical symptoms. However, no significant changes in the levels of inflammatory cytokines in blood serum were detected ( Hossein-khannazer et al, 2021 ; Vieujean et al, 2022 ).…”
Section: Specific Sections Dedicated To Pnd Applicationsmentioning
confidence: 97%
“…In addition, clinical studies have demonstrated that autologous or allogeneic adipose‐derived MSCs exert promising therapeutic effects on anal fistulae, closely related to fibrosis 121,122 . In a recent phase I–II clinical study, local injections of MSCs were found to reverse intestinal fibrosis and resolve intestinal stenosis 123 . This effect was most likely dependent on their immunoregulatory effects and inhibition of TGF‐β signaling 124 demonstrating an exciting prospect of simultaneous anti‐inflammatory and anti‐fibrosis effects from MSC therapies.…”
Section: Prospectsmentioning
confidence: 99%
“…121,122 In a recent phase I-II clinical study, local injections of MSCs were found to reverse intestinal fibrosis and resolve intestinal stenosis. 123 This effect was most likely dependent on their immunoregulatory effects and inhibition of TGF-β signaling 124 demonstrating an exciting prospect of simultaneous anti-inflammatory and anti-fibrosis effects from MSC therapies. EVs derived from MSCs may also regulate intestinal fibrosis through cargo loading.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The results showed that clinical remission might be sustained in the long term and no apparent new safety signals were identified[ 78 ]. In the latest phase I-II pilot trial, local MSC injection may also help resolve CD strictures[ 79 ]. However, using MSCs to promote ulcer healing and repair the epithelial barrier has not been confirmed by clinical trials and more studies are awaited.…”
Section: Epithelial Barrier Repairmentioning
confidence: 99%